Inherited platelet disorders: Insight from platelet genomics using next-generation sequencing. (2nd January 2017) - Maclachlan, Annabel; Watson, Steve P.; Morgan, Neil V.
Abstract: Inherited platelet disorders (IPDs) are a heterogeneous group of disorders associated with normal or reduced platelet counts and bleeding diatheses of varying severities. The identification of the underlying cause of IPDs is clinically challenging due to the absence of a gold-standard platelet test, and is often based on a clinical presentation and normal values in other hematology assays. As a consequence, a DNA-based approach has a potentially important role in the investigation of these patients. Next-generation sequencing (NGS) technologies are allowing the rapid analysis of genes that have been previously implicated in IPDs or that are known to have a key role in platelet regulation, as well as novel genes that have not been previously implicated in platelet dysfunction. The potential limitations of NGS arise with the interpretation of the sheer volume of genetic information obtained from whole exome sequencing (WES) or whole genome sequencing (WGS) in order to identify function-disrupting variants. Following on from bioinformatic analysis, a number of candidate genetic variants usually remain, therefore adding to the difficulty of phenotype–genotype segregation verification. Linking genetic changes to an underlying bleeding disorder is an ongoing challenge and may not always be feasible due to the multifactorial nature of IPDs. Nevertheless, NGS will play a key role in our understanding of the mechanisms of platelet function and the genetics involved.